Aspiration and dysphagia screening in acute stroke – the Gugging Swallowing Screen revisited. (3rd February 2017) - Warnecke, T.; Im, S.; Kaiser, C.; Hamacher, C.; Oelenberg, S.; Dziewas, R.
Abstract : Background and purpose: The Gugging Swallowing Screen (GUSS) is a tool to screen aspiration risk in acute stroke. We aimed to replicate its validity in a larger second cohort of patients with acute stroke, including the more severe with a National Institutes of Health Stroke Scale (NIHSS) ≥ 15. Methods: In a prospective, double‐blind design, the GUSS was validated with the Fiberoptic Endoscopic Evaluation of Swallowing scale. Patients were categorized into different stroke severities as assessed by the NIHSS, and the diagnostic properties were calculated separately for each subgroup. Results: A total of 100 patients with acute stroke were evaluated consecutively at a mean 1.7 ± 2.2 days after stroke. With the GUSS cut‐off value of 14 points, the GUSS screened aspiration risk with a 96.5% sensitivity and 55.8% specificity (area under the curve, 0.76; 95% CI, 0.67–0.84), which corresponded well with the original publication. In the NIHSS < 5 group, the sensitivity and specificity levels were 71.4% and 88.8%, respectively. In the NIHSS ≥ 15 group, these levels changed to 100% and 20%, respectively. The high failure rate in completing the first part of the GUSS in the latter group was related to the low specificity. Diet recommendations following the GUSS were more conservative than those after Fiberoptic Endoscopic Evaluation of Swallowing. In particular, the GUSS overestimated the need for nasogastric tube feeding. Conclusions: This is the first time that a swallowing screening tool for patients with acute stroke has been revalidated in a larger population from another stroke center. The validity of a swallow screening test may vary according to different stroke severities.